FINANCIAL INCLUSION AND PERFORMANCE OF MICRO, SMALL AND MEDIUM SCALE ENTERPRISES IN NIGERIA - Ina Ibor, Bassey; Offiong, Amenawo Ikpa; Mendie, Enyeokpon Samuel (International Journal of Research -GRANTHAALAYAH, 2017)
Financial inclusion assures easy access to financial services by enabling the disadvantaged and vulnerable sections of the society to actively contribute to development and protect themselves against socio-economic shocks. Nigeria has a sizeable rural poor population with limited access to conventional financial institutions or services. This study investigated the impact of financial inclusion on the micro, small and medium enterprises (MSMEs) performance in Nigeria. The survey research design method was used, involving the use of questionnaires, in collecting data from respondents. Data were analyzed using the Pearson Chi-square technique. The results show that, whereas financial inclusion positively and significantly impacts the operations and growth of MSMEs, distance to financial services access points and infrastructural deficiency challenged fast and effective access to financial services by MSMEs in Nigeria. The study recommends that deliberate efforts should be made to spread access points to more rural areas and improve infrastructure to promote FI. This should include a policy roadmap for expanding financial services access points to unbanked and underserved areas using the financial services geospatial map. Furthermore, the digitizing of payments across the country should be prioritized to include enhanced ICT/E-banking tools and a consumer protection framework.